MUHAMMADIYAH COMMUNITY PERCEPTIONS OF THE PRACTICE OF THE TAHLILAN TRADITION IN KOTO TINGGI VILLAGE - Ahmad Karim Siregar (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2025)
Tahlilan tradition is a religious practice that has become an integral part of Indonesian culture, including in Koto Tinggi Village. However, in the context of the Muhammadiyah community, approaches to this tradition often encounter different understandings and interpretations. This research aims to explore the perception of the Muhammadiyah community towards the tahlilan tradition in Koto Tinggi Village. A qualitative research method was employed by conducting in-depth interviews with various members of the Muhammadiyah community with diverse backgrounds and social standings. Data analysis revealed variations in the Muhammadiyah community's views on the tahlilan practice, ranging from those who consider it an integral part of worship and social solidarity to those who criticize it as bid'ah or a religious practice not in accordance with Islamic teachings. The findings of this research provide insights into the dynamics of religious thought and practices within the Muhammadiyah community in Koto Tinggi Village, as well as depict the important role of dialogue and mutual understanding in addressing differences in religious interpretations within a multicultural society. This research contributes to understanding the complexity of religious dynamics in Indonesia, particularly in the context of the tahlilan tradition among the Muhammadiyah community.